Pelvic Bone Deformity and Its Correlation with Acetabular Center-edge Angle - Bruno Dutra Roos; Milton Valdomiro Roos; Antero Camisa Júnior; Ezequiel Moreno Ungaretti Lima; Darby Lira Tisatto; Marcel Cruz Argoud (Revista Brasileira de Ortopedia)
Abstract Objective The purpose of the present study was to evaluate the pelvic bone deformities and its correlation with the acetabular center-edge (CE) angle. Methods Between August 2014 and April 2015, we prospectively evaluated patients aged between 20 and 60 years old. The exclusion criteria were: metabolic disease, previous hip or spine surgery, radiograph showing hip arthrosis ≥ Tönnis two, severe hip dysplasia, global acetabular overcoverage, acetabular crossover sign, hip deformities from slipped capital femoral epiphysis (SCFE) or Leg-Perthes-Calveé, and bad quality radiographs. At anteroposterior (AP) pelvic radiographs, we have evaluated: the CE angle, the acetabular index (IA), the acetabular crossover sign, the vertical and horizontal superior and inferior pelvic axis (H1: Horizontal line 1, superior pelvic axis; H2: Horizontal line 2, superior pelvic axis; V1: Vertical line, superior pelvic axis; HR: Horizontal line, inferior pelvic axis; VR: Vertical line, inferior pelvic axis). The superior and inferior pelvic axis were considered asymmetric when there was a difference ≥ 5 mm between both sides. Patients were divided into two groups: control and group 1. Results A total of 228 patients (456 hips) were evaluated in the period. According to the established criteria, 93 patients were included. The mean age was 39.9 years old (20 to 60 years old, standard deviation [SD] = 10,5), and the mean CE angle in the right hip was 31.5º (20 o to 40º), and in the left 32.3º (20 o to 40º). The control group had 38 patients, with asymmetric H1 in 4 cases (10.5%), H2 in 5 (13.1%), V1 in 7 (18.4%), HR in 5 (13.1%) and VR in 1 (2.63%). Group 1 had 55 patients, with asymmetric H1 in 24 cases (43.6%), H2 in 50 (90.9%), V1 in 28 (50.9%), HR in 16 (29.09%) and VR in 8 (14.5%). Comparing both groups, there was statistical significance for H1, H2 and V1 asymmetry (p < 0.001). Conclusion In the present paper, we observed the correlation between variation in the acetabular CE angle and asymmetry of the superior hemipelvis. The present authors believe that a better understanding of the pelvic morphologic alterations allows a greater facility in the diagnosis of hip articular deformities.